Oral Gene Therapy of HFD-Obesity via Nonpathogenic Yeast Microcapsules Mediated shRNA Delivery - Li Zhang; Wan Zhang; Hang Peng; Yankun Li; Tongtong Leng; Chenxi Xie; Long Zhang (MDPI AG, 2021)
Obesity is a chronic systemic inflammatory disease, which occurs when energy intake exceeds the energy consumption. Therefore, controlling energy intake or increasing physical consumption can effectively control obesity. However, in reality, it is very difficult for the majority of obese patients to lose weight by autonomously controlling diet. In this study, oral shRNA/yeast microcapsules were constructed with non-virus-mediated IL-1β shRNA interference vectors and non-pathogenic Saccharomyces cerevisiae. Moreover, high-fat diet induced obese mice were established to assess the weight loss effect of IL-1β shRNA/yeast microcapsules via the oral route. After IL-1β shRNA/yeast treatment, body weight and fat weight was reduced. Compared with the control group, higher average food intake but lower energy conversion rate was observed in IL-1β shRNA/yeast group. In addition, lipid metabolism related cytokines and blood glucose concentration in the circulating blood was improved after IL-1β shRNA/yeast treatment. Yeast microcapsules mediated IL-1β shRNA delivery can effectively improve obesity. Noteworthy, this kind of non-diet-controlled weight loss strategy does not need diet control, and shows good biocompatibility. It is good news to obese patients who need to lose weight but cannot control their diet.